Alpha-sarcin cleavage of ribosomal RNA is inhibited by the binding of elongation factor G or thiostrepton to the ribosome. - Miller, S P (1991)
The translocation reaction catalyzed by elongation factor G (EF-G) is inhibited either by alpha-sarcin cleavage of 23S rRNA or by the binding of thiostrepton to the E. coli ribosome. Here we show that the transitory binding of EF-G and GDP to the ribosome inhibited the rate of alpha-sarcin cleavage and that stabilization of this binding with fusidic acid completely prevented alpha-sarcin cleavage. A similar pattern of inhibition was seen upon the binding of elongation factor 2 to the S. cerevisiae ribosome. The irreversible binding of the antibiotic thiostrepton to the E. coli ribosome, on the other hand, decreased the rate of cleavage by alpha-sarcin approximately 2-fold. These results suggest that the alpha-sarcin site is located within the ribosomal domain for EF-G binding and that the conformation of this site is affected by the binding of thiostrepton.